Knowledge management framework for teacher professional development: Integrating e-learning innovation in economics education - Lempas, Jety Deisye; Makaliwe, Niny; Tiwow, Gilly Marlya (Universitas Jambi, Indonesia, 2025)
This research aims to develop and validate a comprehensive knowledge management framework to improve teacher professional development and build capacity for introducing innovations to learning economics. The data were collected using quantitative research design with a cross-sectional survey of a sample of 401 secondary school economics teachers and analyzed using SEM-PLS. It is found that when the readiness for digital transformation exists, the knowledge management processes (65.3% and 60.6%) contribute to pedagogical enhancement and knowledge adoption among teachers. The contributions of this study to the literature are as follows: (1) This work involves studying how knowledge management processes mediate the relationship between digital transformation readiness and teacher professional development outcomes, and (2) it validates an integrated framework with good explanatory power and predictive relevance. However, it is found that if the full benefits of e-learning are to be realized, there must be a well-integrated technological infrastructure and organizational support, together with the teachers’ digital literacy.